A generalized method for quantification of cognitive radio benefits within wireless systems - Marshall, Preston Fairfax (Trinity College (Dublin, Ireland). Department of Electronic & Electrical Engineering, 2009)
For most of the history of wireless communications, the primary enabler of enhanced radio communications capability and utility has been continual improvement in the implementing technology and the corresponding ability to exploit a wider range of frequencies, provide complex signaling, and perform coding and error correction.
Keywords: Electrical & Electronic Engineering, Ph.D.; Ph.D. Trinity College Dublin.